Formulation and Evaluation of Moringa Leaf Ethanol Extract Emulgel and its Effectiveness Test Against Staphylococcus aureus - Raissa, Talitha Hasna; Pratiwi, Eskarani Tri; Hidayati, Agriana Rosmalina (Jurnal Biologi Tropis, 2024)
Moringa leaves (Moringa oleifera Lamk.) have Tannin compounds which are secondary metabolites as antibacterial. The purpose of this study is to determine the antibacterial properties of ethanol extract from moringa leaves against Staphylococcus aureus. The research methods began with the extraction of Moringa leaves using sonication with 96% ethanol as the solvent, followed by testing the antibacterial effectiveness of the extract at concentrations of 5%, 10%, and 20%. The extract concentration with the best inhibition zone diameter was formulated into an emulgel, followed by physical evaluation of the formulation and testing its effectiveness against Staphylococcus aureus. The bacterial inhibition zone was measured to determine the antibacterial level of the extract and emulgel formulation. The results of antibacterial effectiveness were evaluated using the One Way ANOVA test with a confidence level of 95%. The yield of the extract was found to be 13.05%. The inhibition zone diameters for the ethanol extract of Moringa leaves at concentrations of 5%, 10%, and 20% were 4.8 mm, 5.3 mm, and 8.1 mm, respectively. The physical evaluation of the ethanol extract emulgel formulation met the criteria for a good emulgel. The emulgel containing 4% ethanol extract from Moringa leaves produced an inhibition zone diameter of 4.8 mm, indicating weak antibacterial effectiveness. There was a significant difference between the treatment groups according to the results of the One Way ANOVA test with a significance value (p=0.000). This study found that Moringa oleifera leaf ethanol extract has the ability as an antibacterial; however, its effectiveness decreases when formulated into an emulgel, likely due to the reduction in extract concentration in the final formulation.